لترقية قدرة الطالبات على فهم المقروء بمعهد إنسان قرآني آتشيه بسار Quantum Reading تطبيق أسلوب - Izzah Febilia, Nurul; Muslim, Buhori; Ninoersy, Tarmizi (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
Reading is an important element in the process of learning Arabic and is one of the language skills. Reading helps students to absorb knowledge and increase interest in writing. Then qiraah can improve students' knowledge with vocabulary, sentences, and editors that can be used in speaking and writing skills. The fahmul maqruk is one of the subjects in the Insan Qur'ani boarding school which aims to enrich students in understanding the reading text. Through observations that the researchers did, it was found that second grade students of the senior high school did not yet master Arabic, especially reading skills. They can read Arabic texts, but do not understand it and are they are unable to answer quetions in the book text. Although the teacher has explained them some of the vocubulary in the book related to the text. This study aims to find out response of teacher and students at Insan Qur’ani Islamic Boarding School in teaching the language using this model and to find out the effectiveness of Quantum Reading model implementation to improve students in reading comprehension. The research method of this study is experimental research. Researcher conducted this study in a group called “One Group Pre-Test Post Test Design”. The result of this research is the teacher and students response in reading teaching using this model is excellent with the achievement of observation value of teacher activity is P = 87,5% between 81-100% with excellent category and observation value of students activity is P = 82,5% between 81-100% with excellent category too. And the aplication of this model effectuve to improve students’ ability in reading comprehension, the proof is that the value of T-test with p -value sig. (2-tailed) is smaller than the value of alpha ⍺ = 0,05 or (T-test < ⍺ = 0,05) with value is (0,000 < 0,05).